TINJAUAN YURIDIS PERMASALAHAN DAN AKIBAT HUKUMNYA ATAS KEPUTUSAN MAJELIS PENGAWAS NOTARIS SEBAGAI OBJEK GUGATAN DI PENGADILAN TATA USAHA NEGARA - Andri Swasono; Gunarto Gun (Jurnal Akta, 2017)
Research with a title “Juridical Review The Problems And The Legal Consequences Of The Decision Of Notary Supervisory Board As The Object Of Lawsuit In Administrative Court” examine the issues arising from the decision issued by the notary supervisory board whether it is a state administrative decision.The decision of the notary supervisory board is an administrative decision which can be used as the object of lawsuit in state administrative court as referred to in the terms of the state administrative decision, namely a written stipulation issued by the agency / officials of state administration which contains administrative legal action based on laws and regulations, which is a concrete, individual, and final, and have a legal effect on a person or civil legal entity.To be able to become the object of a lawsuit after first ensured it is not a state administrative decision which is exempted as meant in Article 2 and Article 49, and shall be ensured that all administrative efforts have been taken.Keywords: notary supervisory board, state administrative decision, object of lawsuit.